The backbone of research in modern education in the context of the competence approach; SHS Web of Conferences; Vol. 28 : Research Paradigms Transformation in Social Sciences (RPTSS 2015) - Raitina M. Margarita; Yurmazova T. A. Tatyana Aleksandrovna; Plankina M. Marina; Raitin M. Maksim (2016, 2016)
Title screen